Eksplorasi Perlindungan Kekayaan Intelektual Komunal Berbasis Hak Asasi Manusia - Diah Imaningrum Susanti (Media Iuris, 2022)
AbstractThis article explores the various scattered rules and their protections for Communal Intellectual Property Rights (KIK) within the framework of law and human rights (HAM) which include Traditional Cultural Expressions, Geographical Indications, Traditional Knowledge, and Genetic Resources. The aim is to determine the adequacy of Indonesia’s positive law in providing legal protection, both defensive and positive, as well as the human rights base in the KIK. The method used is normative juridical, with primary legal material, secondary legal material, which is analyzed using the hermeneutic circumference method, with linguistic and phenomenological analysis to obtain a comprehensive understanding of the protection of the right to KIK within the framework of law and human rights. The research findings show that: the inadequate legal protection for KIK in Indonesia is caused by the duality of nomenclature, recording, and institutional authorities that handle KIK. In addition, the concept of human rights as a claim right, privilege, immunity, power for KIK has not been identified in the KIK rules. A comprehensive and integrated legal protection model is needed for various types of communal intellectual property for the preservation of cultural heritage and national identity within the framework of human rights. Keywords: Business; Communal Intellectual Property Rights; Exploration; Human Rights; Protection. AbstrakArtikel ini mengeksplorasi berbagai aturan yang tersebar dan perlindungannya bagi Hak Kekayaan Intelektual Komunal (KIK) dalam kerangka hukum dan hak asasi manusia (HAM) yang meliputiEkspresi Budaya Tradisional, Indikasi Geografis, Pengetahuan Tradisional, dan Sumber Daya Genetik. Tujuannya adalah untuk mengetahui kememadaian hukum positif Indonesia dalam memberikan perlindungan hukum, baik yang bersifat defensif maupun positif, juga basis HAM dalam KIK tersebut. Metode yang digunakan adalah yuridis normatif, dengan bahan hukum primer, bahan hukum sekunder, yang dianalisis menggunakan metode lingkar hermeneutika, dengan analisis linguistik dan fenomenologis untuk mendapatkan pemahaman yang komprehensif tentang perlindungan hak atas KIK dalam kerangka hukum dan HAM. Temuan penelitian menunjukkan bahwa: belum memadainya perlindungan hukum bagi KIK di Indonesia disebabkan oleh adanya dualitas nomenklatur, pencatatan, dan otoritas kelembagaan yang menangani KIK. Selain itu, konsep HAM sebagai claim right, privilege, immunity, power bagi KIK masih belum teridentifikasi dalam aturan KIK. Diperlukan model perlindungan hukum yang mengatur secara komprehensif dan terintegrasi atas berbagai jenis kekayaan intelektual komunal demi dilestarikannya warisan budaya dan jati diri bangsa dalam kerangka HAM. Kata Kunci: Bisnis; Eksplorasi; HAM; Kekayaan Intelektual Komunal; Perlindungan.